Pan-Cancer Bioinformatics Analysis of Gene UBE2C - Yuan, Lin; Yang, Zhenyu; Zhao, Jing; Sun, Tao; Hu, Chunyu; Shen, Zhen; Yu, Guanying (Frontiers in Genetics, 2022)
Ubiquitin-Conjugating Enzyme E2 C (UBE2C) is a gene that encodes protein. Disorders associated with UBE2C include methotrexate-related lymphatic hyperplasia and complement component 7 deficiency. The encoded protein is necessary for the destruction of mitotic cell cyclins and cell cycle progression, and may be involved in cancer progression. In this paper, on the basis of public databases, we study the expression differential mechanism of gene expression of UBE2C in various tumors and the performance of prognosis, clinical features, immunity, methylation, etc.